Future changes in New Zealands hill country pasture weeds - Popay, A.I.; Rahman, A.; James, T.K. (New Zealand Plant Protection, 2002)
This paper examines the current and possible future status of weed problems in hill country pastures in New Zealand Factors like lower fertiliser inputs stocking rates rural depopulation and changing land use that have affected pastures and pasture management in recent years were assessed The possible effects of climate change on pastures and weed invasions were also considered In addition farmers Regional Councils chemical companies and other stakeholders were surveyed for their opinions on existing and increasingly important weed problems Survey results indicated a resurgence of woody weeds in hill country probably as a result of lower fertiliser input/stocking rates and changing livestock classes due to marginalisation of hill country farming There were few indications of any new weed species appearing in hill country pastures Suggestions were made for increasing surveillance efforts to assist in the early detection of newly emerging weeds in pastures